Strengthening emotional intelligence in developing the madrasah teachers’ professionalism - Tambak, Syahraini; Ahmad, M. Yusuf; Desi Sukenti, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study is to analyze contributions of emotional intelligence in developing professionalism of madrasah. A total of 320 teachers was in volvedas the sample of this study consisted of public and private Madrasah Aliyah teachers in 12 districts/cities throughout Riau Province, Indonesia. This study utilized ex post facto research approach in quantitative research design. Data were analyzed using descriptive and inferential statistics. The results showed that the level of emotional intelligence was high while professionalism was low. There was no effect of gender on the emotional intelligence of the teachers, as well as the teacher’s age, while certification and teaching duration have an impact on the emotional intelligence. Teacher who is over 5 years of certification has a high emotional intelligence, and who teach between 21-30 years have a high level of emotional intelligence. There is no influence of gender in developing the professionalism of madrasah teachers, while teacher age, certification, and teaching duration have an influence. The ages of teacher between 41-50 have a high professionalism and teacher who are over 5 years of certification have high professionalism, and teachers with 20-30 years of teaching experience have high professionalism. Emotional intelligence had a small but significant contribution to professionalism. This study supported the formation of prevention modules and the intervention of teacher professionalism through emotional intelligence elements.